Public shelters: towards secure urban planning and designing in terms of passive defense - Shakibamanesh, Amir (Faculty of Social Sciences and Humanities, UKM,Bangi, 2015)
Recent wars show that enemies in war situations did not always observe international laws or conventions such that cities and their inhabitants were under threats of demolition and destruction. Today, countries which experienced such demolition and destruction would have to pay special attention to passive defense strategies in order to maintain their national capital and vital recourses. Passive defense considerations in urban planning and design may help in reducing damages of cities and the loss of life and property while at the same time enhancing the thresholds of citizen resistance in attack situations and facilitating city crisis management. Urban shelters thus have an important role to play in protecting people against enemy aggressions and should thus be considered as an effective security measure. This article examines some passive defense strategic considerations in the designing and planning of urban shelters, in particular, for countries which have critically strategic and sensitive locations and are prone to threats by covetous expansionist powers.